Learning‐based T‐sHDP(λ) for optimal control of a class of nonlinear discrete‐time systems. (24th October 2021) - Yu, Luyang; Liu, Weibo; Liu, Yurong; Alsaadi, Fawaz E.
Abstract: This article investigates the optimal control problem via reinforcement learning for a class of nonlinear discrete‐time systems. The nonlinear system under consideration is assumed to be partially unknown. A new learning‐based algorithm, T ‐step heuristic dynamic programming with eligibility traces ( T ‐sHDP( λ )), is proposed to tackle the optimal control problem for such partially unknown system. First, the concerned optimal control problem is turned into its equivalence problem, that is, solving a Bellman equation. Then, the T ‐sHDP( λ ) is utilized to get an approximate solution of Bellman equation, and a rigorous convergence analysis is also conducted as well. Instead of the commonly used single step update approach, the T ‐sHDP( λ ) stores finite step past returns by introducing a parameter, and then utilizes these knowledge to update the value function (VF) of multiple moments synchronously, so as to achieve higher convergence speed. For implementation of T ‐sHDP( λ ), a neural network‐based actor‐critic architecture is applied to approximate VF and optimal control scheme. Finally, the feasibility of the algorithm is demonstrated by two illustrative simulation examples.